Effect of crizotinib on overall survival in patients with advanced non-small-cell lung cancer harbouring ALK gene rearrangement: a retrospective analysis - Shaw, Alice T (2011)
BACKGROUND: ALK gene rearrangement defines a new molecular subtype of non-small-cell lung cancer (NSCLC). In a recent phase 1 clinical trial, the ALK tyrosine-kinase inhibitor (TKI) crizotinib showed marked antitumour activity in patients with advanced, ALK-positive NSCLC. To assess whether crizotinib affects overall survival in these patients, we did a retrospective study comparing survival outcomes in crizotinib-treated patients in the trial and crizotinib-naive controls screened during the same time period. METHODS: We examined overall survival in patients with advanced, ALK-positive NSCLC who enrolled in the phase 1 clinical trial of crizotinib, focusing on the cohort of 82 patients who had enrolled through Feb 10, 2010. For comparators, we identified 36 ALK-positive patients from trial sites who were not given crizotinib (ALK-positive controls), 67 patients without ALK rearrangement but positive for EGFR mutation, and 253 wild-type patients lacking either ALK rearrangement or EGFR mutation. To assess differences in overall survival, we assessed subsets of clinically comparable ALK-positive and ALK-negative patients. FINDINGS: Among 82 ALK-positive patients who were given crizotinib, median overall survival from initiation of crizotinib has not been reached (95% CI 17 months to not reached); 1-year overall survival was 74% (95% CI 63–82), and 2-year overall survival was 54% (40–66). Overall survival did not differ based on age, sex, smoking history, or ethnic origin. Survival in 30 ALK-positive patients who were given crizotinib in the second-line or third-line setting was significantly longer than in 23 ALK-positive controls given any second-line therapy (median overall survival not reached [95% CI 14 months to not reached] vs 6 months [4–17], 1-year overall survival 70% [95% CI 50–83] vs 44% [23–64], and 2-year overall survival 55% [33–72] vs 12% [2–30]; hazard ratio 0·36, 95% CI 0·17–0·75; p=0·004). Survival in 56 crizotinib-treated, ALK-positive patients was similar to that in 63 ALK-negative, EGFR-positive patients given EGFR TKI therapy (median overall survival not reached [95% CI 17 months to not reached] vs 24 months [15–34], 1-year overall survival 71% [95% CI 58–81] vs 74% [61–83], and 2-year overall survival 57% [40–71] vs 52% [38–65]; p=0·786), whereas survival in 36 crizotinib-naive, ALK-positive controls was similar to that in 253 wild-type controls (median overall survival 20 months [95% CI 13–26] vs 15 months [13–17]; p=0·244). INTERPRETATION: In patients with advanced, ALK-positive NSCLC, crizotinib therapy is associated with improved survival compared with that of crizotinib-naive controls. ALK rearrangement is not a favourable prognostic factor in advanced NSCLC.